THE EFFECT OF GAMIFICATION ON MARKETING PERFORMANCE: A LITERATURE STUDY - Suadi Sapta Putra; Resti Hardini; Rahayu Lestari; Kumba Digdowiseiso; Sarina Ismail (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
This study investigates the impact of gamification on marketing performance using a systematic literature review methodology. The research background is grounded in the intricate nature of contemporary market dynamics and shifts in consumer behavior, necessitating inventive approaches in marketing strategy. The Systematic Literature Review method is employed to collate and scrutinize pertinent discoveries in associated scientific literature, encompassing empirical research, marketing theory, and the most recent industry trends. The research demonstrates that gamification has a substantial and favorable influence on marketing performance. Game elements, such as incentives, competitions, and rewards, enhance consumer engagement, stimulate purchases, and foster brand loyalty. Literature findings also emphasize the possibility of experiencing gamification fatigue and the danger of exacerbating negative perceptions if not properly controlled. Optimal results can be achieved by striking the right balance between gamification creativity and brand integrity. The research findings validate that the implementation of gamification can enhance marketing performance. However, companies must be cognizant of potential risks and prudently mitigate them. This study enhances comprehension of the correlation between gamification and marketing performance, and offers practical recommendations for companies to create successful marketing strategies in the digital age.